Bridging the information gap between isotope ratio mass spectrometry and conventional mass spectrometry - Meier-Augenstein, Wolfram; Brand, Willi; Hoffmann, Georg F.; Rating, Dietz (Journal of mass spectrometry, 1994)
An isotope ratio mass spectrometer and an ion trap mass spectrometer were coupled in parallel to one gas chromatograph. This system provides the means to obtain information about both chemical nature and isotopic composition of a given compound under identical gas chromatographic conditions.
Gesehen am 28.10.2025